KELAYAKAN FINANSIAL USAHA AGROINDUSTRI BAWANG GORENG UNTUK MENINGKATKAN PENDAPATAN MASYARAKAT KECAMATAN SELAPARANG, KOTA MATARAM - Rucitra Widyasari; Agriananta Fahmi Hidayat; Zulhan Widya Baskara; Zulhan Widya Baskara (Agroindustrial Technology, University of Trunojoyo Madura, 2020)
The financial feasibility analysis in Dutra fried onion microbusiness is carried out in addition to looking at potential for business development in densely populated areas in the city of Mataram as well as to predict the possible obstacles and opportunities that can occur in the future, so this analysis can help increase group income by at least 10 percent. Some things that are reviewed and in the financial feasibility analysis include investment and production costs, cost of goods sold, and business eligibility criteria which include Annual Equivalent (AE), Net Present Value (NPV), Payback Period (PP), and B / C Returns Ratio. The result of the calculation of the financial feasibility of Dutra’s microbusiness is AE IDR 16.153.600, NPV IDR 42.392.660, Payback Perode for 2 years, and B / C Ratio 1.39 in the first year based on financial asset. From these results it can be concluded that a micro business that is feasible to do and if supported by the right marketing process it is not impossible to become a small business icon in this region.